Multimeric antibodies with increased valency surpassing functional affinity and potency thresholds using novel formats. Issue 1 (1st January 2020) - Miller, Ami; Carr, Stephen; Rabbitts, Terry; Ali, Hanif
ABSTRACT: The success of therapeutic antibodies is largely attributed for their exquisite specificity, homogeneity, and functionality. There is, however, a need to engineer antibodies to extend and enhance their potency. One parameter is functional affinity augmentation, since antibodies matured in vivo have a natural affinity threshold. Generation of multivalent antibodies is one option capable of surpassing this affinity threshold through increased avidity. In this study, we present a novel platform consisting of an array of multivalent antibody formats, termed Quads, generated using the self-assembling tetramerization domain from p53. We demonstrate the versatility of this tetramerization domain by engineering anti-tumor necrosis factor (TNF) Quads that exhibit major increases in binding potency and in neutralizing TNF-mediated cytotoxicity compared to parental anti-TNF molecules. Further, Quads are amenable to fusion with different binding domains, allowing generation of novel multivalent monospecific and bispecific formats. Quads are thus a novel group of molecules that can be engineered to yield potential therapeutics with novel modalities and potencies.